DiOjekin!: mobile apps ojek online system for disabilities / Yusuf Gladiensyah ... [et al.] - Gladiensyah, Yusuf; Sukamto, Anjas Pramono; Alayasi, Mutia; Karidina, Sinta; Zunaedi, Prima Ardiansyah (Universiti Teknologi MARA, Kedah, 2019)
Disability is a condition which restrict everyday activities. It substantially affect a person daily activity which can be present from birth or occur during its lifetime. The examples of disability are physically disabled, mute and deaf. In Indonesia physically disabled person or deaf and mute has a problem about mobility from one place to another place in their daily activities, so this problem cause their daily activities are limited. Aside from that, one of a technology that already exist in Indonesia which can solve people with disabilities problem is “Ojek Online”. However, this technology isn’t friendly with people with disabilities because its lack of transportation which support people with disabilities and the drivers didn’t knew about sign language. Therefore, our research conduct by making a new system of “Ojek Online”, disability feature. this feature will solve the people with disabilities problem especially for physically disabled person and mute and deaf from in their daily activities. Actually, this feature inspired from a physically disabled student who need to reach his university on time an easily. People with disabilities need to obtain equality of education same as another people. With this system and disability feature, this system expected facilitate physically disabled person, deaf and mute to start their day easily and also effective.